Promosi Potensi Wisata Desa Bayan Melalui Program Desa Digital - Ngudiyono Ngudiyono; Fika Andriani; Wina Dwi Marianti; Bulan Dwinta Ellyananta; Mikiyal Nurikhsanti; Abdul Mu’in; I Wayan Bagus Widiana; Nizar Zulmi; Tia Farida Rianti; Monika Shanty Ista Purta; M Nur Iskandar; Shofiul Abidin (Universitas Mataram, 2022)
Bayan Village is one of the villages in Bayan District, North Lombok Regency, which consists of 1.530 families with 5.255 people, most of whom work as farmers and ranchers. One of the potentials used by the community is in the tourism sector. Several potentials in the tourism sector in Bayan Village are Bayan Beleq Ancient Mosque, traditional houses, customary forests, terracing areas, Mandala swimming pool columns, and Singang Petune waterfall. However, the tourism potential is still not widely known to the public, so many tourists do not know about the tourism potential in this village. Therefore, through the Thematic Real Work-Study activities, University of Mataram with the theme Digital Village are expected to help the community and village officials in developing and promoting the tourism potential of Bayan Village. The implementation method used is observation, website creation, and socialization. The observations show that there is still a lack of public knowledge regarding the management or use of the internet network for tourism promotion. The attractive potential is still not sufficiently explored. A website has also been created to promote the tourism potential in Bayan Village. As the final stage, there has been socialization about the importance of tourist villages as a catalyst for micro-economic improvement.